PENGARUH VARIABEL FUNDAMENTALTERHADAP HARGA SAHAM PERUSAHAAN FOOD AND BEVERAGE DI BEI - Ardhian, Rheza (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the influence of der, tato and eps variables to the stock exchange at food and beverage companies which are listed in Indonesia Stock Exchange. The samples collection are using nonâprobability sampling with purposive sampling by using certain criteria, then, Indofood is selected as the sample because it is the food and beverage company which includes in the LQ45 index.The research method is using quantitative descriptive with the multiple linear regression analysis. The Analysis Of Variance (ANOVA) test result has obtained the F value of 56.244 with the significance level of 0.018, hence the model obtains is good and able to use for the further analysis. The R square (R2) is 0.988 meaning that the contribution of the independent variable is simultaneous to the dependent variable by 98.8%. On the other hand, the remaining of 1.2% is influenced by other variables which do not include in this regression model.The partial t test result of der is 0.582, tato is 0.072 and eps is 0.049. It shows that the der and tato, partially those variables have no significant, meanwhile, epshas significant influence to the stock price. Keywords: Debt to Equity Ratio, Total Asset Turnover, Earning Per Share, Stock Price.